The Oxford handbook of identities in organizations - Brown, Andrew, 1964- (Oxford handbooks online., 2020)
Conceived as the meanings that individuals attach to their selves, a substantial stockpile of identities-related theorizing, accumulated across the arts, social sciences and humanities over many decades, continues to nourish contemporary research on self-identities in organizations. This handbook offers a comprehensive assessment of current debates and major theories in research on identities in organizations. It provides an interdisciplinary review of the processes of identity construction, how, why, and when such processes occur, and their implications for organizing and individual, group, and organizational outcomes.